Intercultural communication competence from an identity constructionist perspective and its implications for foreign language education - Nguyen, Hoa (H. : ĐHQGHN, 2019)
This paper is aimed at reexamining intercultural communication from an identity social constructionist perspective and offering a linguistically-based research framework. The social constructionist approach holds that knowledge and reality are constructed through discourse, interactions and/or social interchange. This study maintains that language in action as communication in general serves dual purposes. It does not only build the social world, but also constructs identity - a critical issue in our global community recognized by many scholars (as most recently as Jandt, 2016; Fukuyama, 2018). Identity, though, is not just a social construct, but can operate as part of the purpose of communication as well. Recognizing that it is diffcult to fnd clearly-defned methodologies in interdisciplinary areas such as intercultural communication (IC), this study proposes a research framework, grounded in pragmatic theory, and taking speech acts as the basic unit of analysis. The paper also offers implications for foreign language education (FLE) as the nature of FLE is the development of intercultural communication competence (ICC).